Different Causes of Anaemia in Elderly Patients (Medical Forum Monthly, 2024)
Objective: To find out the frequency of dissimilar causes of anemia in elderly patientsStudy Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Department of Haematology, Shaikh Zayed Hospital, Lahore from March 2015 to September 2015.Materials and Methods: A total of 600 cases were enrolled after fulfilling the inclusion criteria. Anemic patients of both genders between 66-86 years were included.Results: Mean age was 73.14±4.05 years. Male patients were in majority 430(71%). Anemia due to iron insufficiency was found in 178 (29.7%) cases, anemia which was related to megaloblastic cause was noted in 72 (12%) cases, myelodysplastic syndrome related anemia in 56 (9.3%), anemia due to chronic inflammation was found in 150 (25%) of cases, 56 (9.3%) of cases had anemia which was caused by chronic kidney disease, anemia which was linked with endocrinopathy was present in 60 (10%) cases and in 28(4.66%) cases anemia was of unexplained origin.Conclusion: The majority of the cases had iron insufficiency related anemia in the elderly age. So it is recommended that iron therapy should be given to the elderly patients.